Wizja Europy Środkowowschodniej w projektach geopolitycznych ideologa eurazjatyzmu, Aleksandra Dugina - Bala, Maciej (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is an attempt to present the views of the Russian thinker on the political situation in the post-Soviet region. In his conception Aleksandr Dugin focuses on geopolitics, international relations and the position ofRussiain the new globalised world. Dugin attempts to undermine the principles of the new world order. He creates ideological foundations which may serve as a justification for regaining the imperial position ofRussia. The foundation of Dugin’s views is Eurasianism combined with the elements of geopolitics. The philosopher creates a blueprint for the Great Eurasian Empire which would compriseEast-Central Europe. According to Dugin, significant political and territorial changes will be conducted in this region on the basis of the religious faith of its inhabitants. The protestant countries will be federalized. Both the Protestant and Catholic countries will become theGermany’s sphere of influence. The Balkan states will have a somewhat different status as they will be federalized into one political subject connected withEurasia.GermanyandRussia, whose position is dominant in this region ofEurope, will become a part of the Great Eurasian Empire. There will be no room left for independentPolandandUkrainein the structure of the Eurasian Empire. Dugin does not take into account economic factors which would convince European states to integrate withEurasia. As for the present day, it is impossible to put the Eurasian project into realization.